Recommendations for planning and delivery of radical radiotherapy for localized urothelial carcinoma of the bladder. (August 2021) - Khalifa, Jonathan; Supiot, Stéphane; Pignot, Géraldine; Hennequin, Christophe; Blanchard, Pierre; Pasquier, David; Magné, Nicolas; de Crevoisier, Renaud; Graff-Cailleaud, Pierre; Riou, Olivier; Cabaillé, Morgane; Azria, David; et al.
Highlights: Homogenized guidelines for bladder radiotherapy were needed in literature. A technical consensus for radiotherapy of bladder cancer is presented. Planning acquisition, PTV margins and lymph-nodes radiotherapy are controversial. Practical recommendations are available for the implementation of novel techniques. Abstract: Purpose: Curative radio-chemotherapy is recognized as a standard treatment option for muscle-invasive bladder cancer (MIBC). Nevertheless, the technical aspects for MIBC radiotherapy are heterogeneous with a lack of practical recommendations. Methods and materials: In 2018, a workshop identified the need for two cooperative groups to develop consistent, evidence-based guidelines for irradiation technique in the delivery of curative radiotherapy. Two radiation oncologists performed a review of the literature addressing several topics relative to radical bladder radiotherapy: planning computed tomography acquisition, target volume delineation, radiation schedules (total dose and fractionation) and dose delivery (including radiotherapy techniques, image-guided radiotherapy (IGRT) and adaptive treatment modalities). Searches for original and review articles in the PubMed and Google Scholar databases were conducted from January 1990 until March 2020. During a meeting conducted in October 2020, results on 32 topics were presented and discussed with a working group involving 15 radiation oncologists, 3 urologists and one medical oncologist. We applied the American Urological Association guideline development's method to define a consensus strategy. Results: A consensus was obtained for all 34 except 4 items. The group did not obtain an agreement on CT enhancement added value for planning, PTV margins definition for empty bladder and full bladder protocols, and for pelvic lymph-nodes irradiation. High quality evidence was shown in 6 items; 8 items were considered as low quality of evidence. Conclusion: The current recommendations propose a homogenized modality of treatment both for routine clinical practice and for future clinical trials, following the best evidence to date, analyzed with a robust methodology. The XXX group formulates practical guidelines for the implementation of innovative techniques such as adaptive radiotherapy.